PERSONALITY FACTORS AND SOCIO-ECONOMIC STATUS AS PREDICTORS OF TENDENCY TO VANDALIZE THE NIGERIAN OIL PIPELINES AMONG IJAW YOUTHS - ABAMARA, Nnaemeka C; EZEH, Leonard Nnaemeka; OGUEGBE, Tochukwu M; NWAAJEI, Emmanuel Patrick (Social Science Research, 2021)
The study investigated personality factors and socio-economic status as predictors of tendency to vandalize Nigerian oil pipelines among Ijaw youth. A total number of two hundred and nineteen (219) youths drawn from five towns (Amassoma, Boma, Ekeni and Ayama) in Oporoms district, Ijaw local government area of Bayelsa State served as the participants for this study. They were selected through systematic sampling technique; their age ranged from 18 – 43 years and their mean ages was 29.35 with standard deviation of 6.87. They consisted of 116 males and 103 females. Two instruments were used ‘’The Big Five Personality Inventory (BFP), a 44 – item scale, which measured the Big Five Factors (dimensions) of personality. Each of the factors is then further divided into personality facets. It was developed by John and Srivastava, (1999), and tendency to vandalize scale (TVS) which contains 18-items and has a reliable internal consistency coefficient. The Hypotheses were tested at p< .05 level of significance. The results of the study indicated in the first hypothesis that openness to experience significantly predicted the tendency to vandalize oil pipeline. Conscientiousness did not significantly predict the tendency to vandalize oil pipeline. Agreeableness did not significantly predict the tendency to vandalize oil pipeline. Neuroticism did not significantly predict the tendency to vandalize oil pipeline. The result of the socio-economic status on the High, Medium and Low did not significantly predict the tendency to vandalize oil pipeline among Ijaw youths. The researcher therefore recommends that the government should ensure the establishment of rehabilitation homes in affected cities, where offenders with predisposing personality traits and vulnerable personality traits to vandalize oil pipeline are kept for observations and reformation.